(untitled) (Bhartiya Knowledge Systems, 2025)
Osteoporosis is a bone disease primarily occur in female. However, men are also affected by the disease. The disease is manifested through the number of factors including hormonal deregulation, deficiency of vitamins and abnormal metabolism. Calcium is one of the essential micronutrients required for the growth and development of bone in human body. The calcium level is elevated in osteoporosis. Therefore, growth of human body is dependent on the dietary intake of calcium. The hormones calcitriol and parathyroid hormone (PTH) control the level of calcium in human and other primates. The 99% of calcium in bone is stored as hydroxyapatite. Constant irregular level of calcium in blood causes the osteoporosis condition. In osteoporosis, density of mineral calcium has been found to be drastically decreased in bones. This in turn, decreases the bone mass. The increase concentration of calcium in blood due to bone desorption might lead to hypercalcemia. In blood circulation, calcium exists in three forms 1) free (ionized form), 2) complexed (chelated form) and 3) protein bound form. Therefore, measuring blood calcium level is important in diagnosing and preventing several diseases. The total calcium level and ionized calcium level are the two tests generally performed on blood sample. Herein, for the first time we are reporting the laboratory based qualitative and quantitative identification test for determination of blood calcium level for osteoporosis disease.